2002
DOI: 10.1381/096089202762552737
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Reoperative Bariatric Surgery: Experience from 27 Consecutive Patients

Abstract: Our results compare favorably with those reported for open reoperative bariatric surgery. A laparoscopic approach may be considered a feasible and safe alternative to an open operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
74
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(87 citation statements)
references
References 22 publications
9
74
0
4
Order By: Relevance
“…Several studies have reported pre-and postopera tive BMI results similar to ours. [14][15][16] Half of all revision patients had a prior VBG. Because of resultant complications and poor weight loss (21%-50%), this procedure was phased out as a primary bariatric procedure many years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported pre-and postopera tive BMI results similar to ours. [14][15][16] Half of all revision patients had a prior VBG. Because of resultant complications and poor weight loss (21%-50%), this procedure was phased out as a primary bariatric procedure many years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Failure is commonly defined as inadequate weight loss and constitutes the primary indication for revisions in most series dealing with revisional bariatric surgery [7,10]. Consensus is that inadequate weight loss is diagnosed in cases where 50% excessive weight loss (EWL) or a BMI <35 is not achieved or maintained in the long term [11].…”
Section: Indications For Reoperationsmentioning
confidence: 99%
“…However, the success rate of the different available operative techniques is not 100%, and failures do occur during follow-up. About 10-25% of patients undergoing bariatric surgery require revisional surgery, mainly due to insufficient weight loss or due to complications from the primary procedure [7,8]. Revisional bariatric surgery can be complex and technically demanding depending on the primary operation and on the indication leading to reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Up to 12% of patients will have some type of surgical revision following gastric bypass surgery due to weight gain or postoperative symptoms related to stomal dilation. 4 Reoperation can present significant technical challenges to the surgeon and result in appreciable morbidity or mortality. 5 Patients who undergo operative revision have a lengthy operation, a major complication rate of 14%, and a mortality rate of 1.3%.…”
Section: Introductionmentioning
confidence: 99%